2019
DOI: 10.1021/acs.jpcb.9b05808
|View full text |Cite|
|
Sign up to set email alerts
|

Modified Entropy Scaling of the Transport Properties of the Lennard-Jones Fluid

Abstract: Rosenfeld proposed two different scaling approaches to model the transport properties of fluids, separated by 22 years, one valid in the dilute gas, and another in the liquid phase. In this work, we demonstrate that these two limiting cases can be connected through the use of a novel approach to scaling transport properties and a bridging function. This approach, which is empirical and not derived from theory, is used to generate reference correlations for the transport properties of the Lennard-Jones 12-6 flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 123 publications
3
138
0
Order By: Relevance
“…Additional data for SCLJ are given in ref. 75 , demonstrating that the same trend continues into the gaseous region.
Fig.
…”
Section: Resultsmentioning
confidence: 80%
“…Additional data for SCLJ are given in ref. 75 , demonstrating that the same trend continues into the gaseous region.
Fig.
…”
Section: Resultsmentioning
confidence: 80%
“…For a new treatment of the entropy scaling characteristics of the transport coefficients of the LJ fluid over the whole density range, see Ref. 56. It has been found that the scaled self-diffusion coefficient and shear viscosity of the LJ fluids are to a very good approximation invariant along an isomorph for densities above approximately the critical value.…”
Section: Introductionmentioning
confidence: 99%
“…For the calculation of viscosities of real fluids, this approach was primarily used in connection with semi-empirical equations such as the PCP-SAFT [42][43][44] or the CPA [45] equation of state. After introducing a modified approach with a dimensionless residual entropy per unit volume as the independent scaling variable and a suitable choice of a reference fluid for refrigerants [46], the approach was first applied to model fluids in conjunction with accurate Helmholtz-energy equations of state [47]. Subsequently, comprehensive studies on pure hydrocarbons were carried out by Bell [48,49].…”
Section: Entropy Scalingmentioning
confidence: 99%